Microstructure and texture evolution during annealing of Ti–6Al–4V alloy. Issue 4 (3rd March 2020) - Debta, M. K.; Bishoyi, B. D.; Sabat, R. K.; Muhammad, W.; Sahoo, S. K.
ABSTRACT: Ti–6Al–4V plates were subjected to warm rolling at 600°C up to 85% reduction in thickness followed by annealing at 850°C for different soak periods. It was observed that the 'β' grains were prevalent along the grain boundaries and at the triple junctions of 'α' grains. The samples were found to be fully recrystallised after 30 min of annealing time. Further, globularizarion of 'α' grains was observed during the progress of annealing. The recrystallisation mechanism was identified to be through sub-grain formation and its growth. A dominant near basal texture, i.e. ( 10 1 ¯ 7 ) < 70 7 ¯ 2 ¯ >, was observed in the samples after annealing.